Retrospective Analysis: Most Common Diagnoses Seen in a Primary Care Clinic and Corresponding Occupational Therapy Interventions - Felicia Trembath; Sue Dahl-Popolizio; Makenzie VanWinkle; Laura Milligan (Scholarworks @ WMU, 2019)
Background: The literature supports occupational therapy (OT) on primary care (PC) interprofessional teams; however, due to uncertainty regarding the role of, and reimbursement for, OT in PC, few occupational therapists practice in PC. This study addressed the first barrier by identifying the 15 most common diagnoses in a specific PC practice and determining how many of them have evidence-based OT interventions appropriate for their treatments. Method: A retrospective analysis of the ICD-10 codes used by one physician during a 12-month period was completed. These codes were reviewed and categorized using a functional classification system to determine the 15 most frequently occurring diagnostic categories. These diagnostic categories were compared to evidence-based industry standard OT interventions. Results: We reviewed 1,769 distinct ICD-10 codes and condensed them into 58 thematically grouped diagnostic categories. The 15 most frequent categories comprised 64% of the codes used. Evidence-based OT interventions to treat conditions directly, or address related underlying issues and common comorbidities, were identified for 100% of these categories. Discussion: Evidence-based OT interventions exist to treat aspects of 100% of the 15 most common conditions seen in PC. The findings support the growing body of literature that demonstrate the use of occupational therapists as interprofessional PC team members.